Aksi Mahasiawa KKN UNP Bangkitkan Semangat Olahraga Pemuda Lewat Turnamen Futsal Campago - Nurhasan Syah; Rahmatul Ilham; Nurlaila Fitri; Nasywa Ayudvi; Mela Armifa; Zahwa Nur Azizah (CV. ITTC INDONESIA, 2026)
The inter-village futsal tournament held in Nagari Campago was one of the contributions of the Community Service Program (KKN) students from Padang State University (UNP) to fostering a spirit of sport among youth. This activity not only encouraged youth participation in sports but also strengthened solidarity and togetherness among village residents. This research used descriptive qualitative methods to explore the active role of the KKN students in facilitating the activity and its impact on the community. The results showed that the presence of the KKN students directly encouraged the creation of a sporting culture and strengthened social bonds among youth in Nagari Campago. Therefore, the involvement of KKN student through a sports-based community approach can serve as an effective model for youth empowerment in other nagari